Students’ perspectives on plagiarism detection - Murugathas, K.; Santharooban, S. (University of Jaffna, 2022)
Plagiarism is a common problem, especially in the electronic information world. It has an adverse impact on academic integrity. Plagiarism has drawn the attention of many academic institutions to implement actions to reduce it. The study aimed to assess the students’ perspectives on plagiarism detection among the final year undergraduates of the Faculty of Allied Health Sciences, University of Jaffna. A cross-sectional survey was conducted using questionnaires among all the final year undergraduates (168) of the Faculty of Allied Health Sciences. The data was analyzed using descriptive statistics, and a one-sample Wilcoxon signed-rank test in SPSS. The results indicated that 86 % of the undergraduates have a good understanding of plagiarism. The majority of the students (90 %) responded that knowledge about plagiarism is an important concept in their study programme. The analysis revealed that the students’ attitudes toward plagiarism detection were significantly positive (p<0.05) and that the students positively perceived the introduction of the plagiarism detection tool in the undergraduate study programme. Eighty-six percent (86 %) of students said the iThenticate detection tool gives them the confidence to write quality reports at the end. The majority of the students (83 %) responded that it was difficult to rewrite the report to reduce the percentage of similarity. The paper concludes with a recommendation that the undergraduate students of Allied Health Sciences need training in academic writing skills and a detailed demonstration of the iThenticate detection tool. The findings of the study can help academics to implement the necessary actions to support students in reducing plagiarism.
Keywords: Plagiarism; iThenticate; Students’ perspectives; Undergraduates; Allied Health Sciences